The Effects of Learning in Interactive Monetary Policy Committees - Jan Marc Berk; Beata K. Bierut (Tinbergen Institute, 2004)
We develop a theoretical framework for studying the effects of interaction on the quaJity of decision-making by monetary policy committees. We show that interaction, i.e. increasing one's expertise through an exchange of views, is most likely not to result in interdependent voting behaviour.Therefore, and in contrast to earlier literature, we find that interaction is beneficial for the collective outcome.
Keywords: E52; E58; D83; D71; 330; Monetary policy; interest rates; learning; Geldpolitik; Gruppenentscheidung; Lernen